Qualidade de vida no trabalho, gestão do conhecimento e sistemas produtivos: estudo em empresas paranaenses do setor metal-mecânico - Miranda, Isabella Tamine Parra (2015)
This study aims to understand the actions that estabelem within the GC to provide QVT, and create a specific model of SP are correlated. Used data collection instruments are based on the model of Walton (1973-1974) for QVT variable in Terra model (1999), for the variable GC and Fordism models, Toyotism and Volvismo for the variable production systems (SP). Full implementation of the instruments was held in the city of Maringa, Parana in a sample of 13 companies, involving 265 workers guaranteed thus a margin of error of 5% and a 95% confidence interval. It was found that there is an inverse correlation between the GC and QWL indicators in the companies investigated regardless of their size. QVT indicators are determinants in the classification of enterprises by size. Medium and small companies have better average of QVT that micro-enterprises and the large investigated. Indicators of GC instruments and SP individually are not decisive in the companies according to size classification. The SP of the evaluated companies is predominantly flexible. The findings of the study suggest that the management practices and production systems of these companies related to effective GC and therefore the encouragement of learning, creativity and innovation in the organizational context are associated with better organizational results. You can improve the rates of QVT considering the combination of the needs of employees and organizational goals. The QVT enables increased productivity.